Resource communication. Individual-tree growth model for radiata pine plantations in northwestern Spain - Crecente-Campo, F.; Dieguez-Aranda, U.; Rodriguez-Soalleiro, R. (Forest Systems, 2012)
Individual-tree basal area and height increment models were developed with data from 130 permanent plots of Pinus radiata D. Don located in Galicia (northwestern Spain). Mixed-models techniques were used for model fitting. Covariates acting at tree and stand level were included as fixed effects. Estimated values of stand variables obtained from aggregation of individual-tree predictions were used in model evaluation. The developed models accounted for 54% of the variability in basal area increment and 36% of the variability in height increment, with mean errors of 16 cm2 and 0.36 m, respectively. These models, along with an existing individual-tree mortality model, constitute a whole individual-tree growth model that can be used to simulate forest management alternatives, helping in forest managers’ decision making.